Competitive advantage, political advantage and shelter in the textile industry - Bowen, G (2004)
The effect of government on competitive advantage theory has only been covered superficially in strategic management literature. This thesis incorporates government into competitive advantage and multinational enterprise (MNE) theory by demonstrating how politically derived firmspecific advantages (FSAs) and competitive advantages may accrue from noncommercial, political sources, to be manifested in commercial enterprises as 'political competitive advantages (PCAs)'. The empirical background to this thesis is a study of the global textile industry and the complexity, multidimensional and multi-level nature of the relationship between the wider textile complex and governments. Examples demonstrate the significant impact of governments upon the textile industry, across the globe and over a wide variety of time horizons. A review of the relevant strategic management and international business core theory forms a base on which the PCA concept is developed. A synthesis of the strategic positioning view (SPV) of competitive advantage, the resource-based view (RBV) and transaction cost/internalization theories is used to develop the PCA concept. MNEs can derive superior operator surpluses (rents) from complex government externalities that, due to their asymmetrical impact, enable some profit-centres to gain PCAs. PCAs are non-market-related, chiefly government-derived, political competitive advantages and form a new subset of firm-specific advantages (FSAs). The international business concept of nonefficiency, shelter-based advantages form a subset of PCAs. An eight-cell PCA analytical framework is developed and operationalized using case studies selected from the world-wide operations of Coats PLC, the world's largest producer and distributor of sewing thread, and one of Britain's oldest MNEs. This analytical framework enables firms to better understand the significant and dynamic nature of those government externalities that have a major impact upon firm efficiency. The framework can be used to assist practitioners in the search for sustainable reactive and/or proactive ( endogenizing) strategies that can enhance PC As and reduce political competitive disadvantages (PCDs ).